3D Virtual Catalogue Of PENS Campus Using Augmented Reality - Kholid Fathoni; Achmad Basuki; Octario Rezkavianto (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2020)
PENS is a vocational education campus that is actively promoting the community to capture the interests of prospective students to register as students. This requires promotion of media innovation that can attract public interest. Multimedia technology, especially augmented reality can be used as an attractive alternative media for PENS to carry out promotions. This study aims to develop promotional media in the form of an augmented reality technology-based virtual catalog to introduce various study programs available in PENS. Catalogs that are generally in the form of physical media are converted into markers that can bring up 3D objects and videos that explain the contents to the user so that the user does not need to read because there is already an audio visual explanatory facility. The trial results show that the PENS virtual catalog can function well in viewing AR mascot, AR video and information.